3D hybrid materials based on zinc and cobalt phthalocyanine derivatives bearing terminal ethynyl substituents as active layers for chemiresistive gas sensors - Ivanova, Victoria; Senocak, Ahmet; Klyamer, Darya; Demirbas, Erhan; Makhseed, Saad; Krasnov, Pavel; Basova, Tamara (Elsevier Science Sa, 2024)
Porous 3D hybrid materials (SWCNT/CoPc and SWCNT/ZnPc) were prepared by the reaction between single walled carbon nanotubes (SWCNT) functionalized with azido groups and ZnPc or CoPc phthalocyanines con-taining 16 terminal ethynyl groups and characterized by various physical methods. It was shown by thermog-ravimetric analysis (TGA) that the number of CoPc molecules attached on the SWCNT surface was one CoPc molecule per 115 carbon atoms, which is larger than in the case of the SWCNT/ZnPc (one ZnPc molecule per 312 carbon atoms). The prepared hybrids were studied as active layers of chemiresistive sensors for the detecting gaseous H2S at low concentrations (0.1-50 ppm). It was found that the sensor response of SWCNT/CoPc was about 4 times higher than in the case of SWCNT/ZnPc, which correlated well with the larger number of CoPc molecules on the SWCNT surface. The prepared hybrids are promising materials for the creation of fully reversible sensors for the detection of H2S at room temperature. The calculated LOD (3 sigma/m) of H2S was 18 and 65 ppb for SWCNT/CoPc and SWCNT/ZnPc, respectively.
Keywords: 3D hybrid materials; Metal phthalocyanines; Gas sensors; Chemiresistive sensors; Ammonia; hydrogen sulfide